Impact and Adaptation of Cyclones on Major Crop Production for Smallholder Farmers in the South-central Coast of Bangladesh (Journal of the Bangladesh Agricultural University, 2026)
Climate change has increased the frequency and intensity of cyclones in Bangladesh's coastal regions, significantly affecting agricultural productivity. Therefore, implementing farm-level adaptation strategies against cyclones is essential to sustain and enhance crop productivity in these vulnerable areas. This study addresses this gap by examining farm-level vulnerabilities, cropping system impacts, and indigenous adaptation strategies across two highly cyclone-vulnerable districts (Patuakhali and Jhalokathi) in the south-central coastal region of Bangladesh. Utilizing a robust multi-stage random sampling design, primary empirical data were collected from 200 strictly screened smallholder households and systematically integrated with multi-decadal secondary meteorological data. The empirical results reveal severe, compounding seasonal disruptions, with Transplanted Aman (T. Aman) rice suffering the highest vulnerability, accounting for over 50% of aggregate cyclonic crop damage. Cyclonic storm surges trigger extensive economic losses averaging BDT 20,000-35,000 (163-285 USD) per household, primarily driven by secondary hazards such as rapid salinity intrusion, soil erosion, and prolonged waterlogging. While 79% to 80% of farmers perceive an accelerating frequency of cyclonic events, their current reactive adaptations (e.g., shifting planting timelines) are heavily constrained by indigenous knowledge and lack structural or technological scaling. Furthermore, 57% to 61% of smallholders identify the lack of institutional support and dedicated financial subsidies as the primary barriers to sustainable adaptation. These findings underscore an urgent need to transition from autonomous, experience-based coping mechanisms toward structural, zone-specific adaptation policies. This research provides a scalable framework for integrating empirical farmer perceptions with scientific weather analytics to engineer climate-resilient coastal agricultural systems globally.J Bangladesh Agril Univ 24(2): 118–128, 2026